The potential role of violet-blue light to preventing hospital acquired infections: a systematic review - Valentina Lucarelli; Davide Amodeo; Isa de Palma; Nicola Nante; Gabriele Cevenini; Gabriele Messina (Frontiers Media S.A., 2024)
Healthcare-associated infections (HAIs) are a major challenge in modern healthcare, leading to increased mortality, financial burden and negative societal impact. The World Health Organization (WHO) and others have highlighted the alarming rise in HAIs, exacerbated by antimicrobial resistance (AMR), which further complicates treatment. The efficacy of violet-blue light (VBL) technology (approximately 405-420 nm) in inactivating various pathogens and its safety for human exposure have been extensively studied. This study analyses the scientific literature on the use of VBL as a disinfection method in health care settings, with cost and safety implications. It discusses VBL in comparison to other disinfection methods, the implications of its use, and its potential in reducing HAIs due to its ability to be used in occupied environments. While UV technology is more effective at bacterial inactivation, the continuous application of VBL compensates for this difference. UV and VBL technologies have a positive environmental impact, eliminating the need for consumables and reducing waste. Safety concerns are very limited for VBL compared to UV when properly used. The literature highlights that implementing VBL can be a significant step in continuous environmental disinfection in both healthcare and domestic settings. VBL is safe for occupants and offers a feasible, green method for combating environmental contamination and potentially reducing HAIs.